2020
DOI: 10.3390/nu12092721
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Wheel Running Effects on High Fat Diet Preference, Metabolic Outcomes, and Performance on the Barnes Maze in Rats

Abstract: Excessive and prolonged intake of highly palatable, high fat (HF) foods contributes to the pathogenesis of obesity, metabolic syndrome, and cognitive impairment. Exercise can restore energy homeostasis and suppress HF diet preference in rats. However, it is unclear if exercise confers similar protection against the detrimental outcomes associated with a chronic HF diet preference and feeding in both sexes. We used our wheel running (WR) and two-diet choice (chow vs. HF) paradigm to investigate the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 132 publications
(199 reference statements)
0
6
0
Order By: Relevance
“…A study examining sex differences in voluntary wheel running has shown that female rats voluntarily run on wheels daily for higher distances compared to males [44]. Similarly, more recent studies have reported higher numbers of daily wheel revolutions in female compared to male rats [47,48], indicative of higher voluntary running activity in female compared to male rodents. Interestingly, ovariectomized 3-month-old female Sprague-Dawley rats run shorter daily distances on wheels compared to ovariectomized rats treated with estrogen replacement, suggesting a potential role of the sex hormone estrogen in running distance [49,50].…”
Section: Exercise Regimens Used In Preclinical Researchmentioning
confidence: 99%
“…A study examining sex differences in voluntary wheel running has shown that female rats voluntarily run on wheels daily for higher distances compared to males [44]. Similarly, more recent studies have reported higher numbers of daily wheel revolutions in female compared to male rats [47,48], indicative of higher voluntary running activity in female compared to male rodents. Interestingly, ovariectomized 3-month-old female Sprague-Dawley rats run shorter daily distances on wheels compared to ovariectomized rats treated with estrogen replacement, suggesting a potential role of the sex hormone estrogen in running distance [49,50].…”
Section: Exercise Regimens Used In Preclinical Researchmentioning
confidence: 99%
“…In this regard, white adipose tissue (WAT) should be considered as an essential variable in the equation of aging-dependent changes favoring the development of chronic liver disease. Moreover, prolonged detrimental eating habits feeding adipocytes sum up over a lifetime [74] to take their toll in old age. The key task of WAT is to maintain energy homeostasis: Upon excess energy availability, it increases lipid storage and systemically communicates nutritional abundance, while releasing stored triglycerides upon energy depletion as free fatty acids to support catabolism.…”
Section: Adipocytes Of White Adipose Tissuementioning
confidence: 99%
“…The BM was first introduced by Carol Barnes in 1979, a few years after the development of the RAM, to study spatial memory in rats [ 64 , 65 ]. To date, it has been primarily applied in small rodents, such as mice [ 65 , 66 , 67 ] and rats [ 68 , 69 , 70 ]. The maze consists of an elevated circular PVC platform (122 cm diameter) supported by an aluminum support frame containing equally spaced holes.…”
Section: Experimental Tools For Assessing Hippocampal-dependent Learn...mentioning
confidence: 99%